Identification of a unique gene cluster of Brucella spp. that mediates adhesion to host cells - Czibener, Cecilia (2012)
Brucella, the causative agent of brucellosis, a major zoonotic disease affecting a broad range of mammals, is a gram-negative bacterium whose virulence is dependent on the capacity to attach and invade different cells of the host. The bacterium is able to infect through a diverse repertoire of epitheliums: skin, airways or gastric. Although much has been studied on the mechanisms Brucella uses to establish an intracellular replication niche, almost none is known on how the bacterium adheres and invades host cells. We report here the identification of a pathogenicity island that harbors a gene homologous to proteins with bacterial immunoglobulin-like domains present in other pathogens that play a role in attachment and invasion. Deletion of the entire island results in a mutant with a reduced attachment capacity measured by intracellular replication and adhesion assays. Intraperitoneal and oral experimental infection of mice strongly suggests that this island plays a role during the oral infection probably mediating attachment and trespassing of the gastric epithelium to establish a systemic infection.